The Magic, the Mountain and the Muti: towards an interpretation of Marikana as marronage - Adams, Robyne (Department of Sociology, 2023)
In the decade since the Marikana massacre, the many scholarly insights into the event tend towards abstracting these strikes into a universalist ‘working-class' discourse. This minor dissertation departs from this analysis, however, by paying attention to repertoires of resistance that connect Marikana with a longer history of collective resistance in South Africa. To do this, I read specific testimonies given during the Marikana commission inquiry and focus on subsets of acts, symbols, languages, phrases and words – all of which point to strong ontological continuities between Marikana and what I believe to be Marikana's pre-history - the 1850's Cattle-Killing Movement, the 1921 Bulhoek Massacre, the 1960s Mpondo Revolts and the 2000s Xolobeni protests. In light of this, I suggest that the Marikana striker's political praxis are indicative of a unique epistemology of resistance - an epistemology that points to a longer and yet, more invisible lineage of black radicalism. With this history of black resistance in mind, I re-read the forms of collective action that unfolded in Marikana - as akin to a specific, but highly overlooked form of flight from oppression - as sociogenic marronage. I argue that the concept of sociogenic marronage helps us plot a genealogy of black resistance and radicalism that is not captured in Eurocentric frames of understanding collective struggles.